PURCHASE DISCOUNTS. - Krebs, W. S. (The Accounting Review, 1926)
Abstract To business men it has long been apparent that concerns which sell exclusively on account are obliged to set their prices at higher levels than those which sell exclusively for cash. Three major reasons are commonly assigned to explain this fact. First, a concern selling exclusively on account requires a larger amount of working capital than one which sells exclusively for cash, which necessitates higher prices or a more rapid turnover or both for the business selling on a credit basis, if Its profits are to be equal to those of the business on a cash basis. Second, a concern which sells exclusively on account find its working capital continually undermined from losses on un-collectible accounts receivable. To show a satisfactory rate of profit, therefore, it is essential that the management charge an estimated insurance premium to compensate for this loss. Third, the concern on a credit basis finds additional expenses incurred in granting credit and In making collections. And on this account, also, businessmen early recognized the necessity for a higher price list when sales were made exclusively on account then that needed when sales were made exclusively for cash.